Association between platelet/high-density lipoprotein cholesterol ratio and blood eosinophil counts in American adults with asthma: a population-based study - Qian Zhao; Peng Yang; Jing-Pan Li; Lei Du; Wei Wang; Si-Xuan Zhu; Shan Wu; Yun-Feng Chen (Lipids in Health and Disease)
Abstract Objective This study aims to evaluate the relationship between the platelet-to-high-density lipoprotein cholesterol ratio (PHR) and blood eosinophil counts (BEOC) in asthmatic patients, using data from the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2018. Methods This research explored the link between PHR and BEOC among adults with asthma, drawing on data from a representative U.S. population sample (n = 3034; NHANES 2011–2018). To assess this relationship, multivariable linear models were employed, alongside subgroup and interaction analyses to identify any potential variations across different groups. Additionally, generalized additive models, smooth curve fitting, and threshold effect analysis were employed to explore the relationships in greater detail. Sensitivity tests were performed to ensure the robustness of the findings. Results The weighted multivariable linear regression analysis showed that after adjusting for all covariables, each one-unit rise in PHR was linked to an increase of 41.61 in BEOC (β: 41.61, 95% CI: 25.25–57.97). Subgroup analyses demonstrated consistency across various categories, reinforcing the significant positive association between PHR and BEOC. Interaction tests indicated that this positive association remained stable regardless of factors such as body mass index, smoking, hypertension, or diabetes, with all interaction P-values greater than 0.05. Additionally, the application of generalized additive models and two-piece linear regression models further confirmed the linear association between PHR and BEOC. Conclusions Our study indicates that a higher PHR may be associated with an increased risk of elevated BEOC in American adults with asthma. Thus, PHR might be considered a potential marker for predicting elevated BEOC levels in this population.